EFFECT OF ENTREPRENEURIAL ORIENTATION AND KNOWLEDGE SHARING ON BUSINESS PERFORMANCE - Eko Putra Sri Sentanu, I Gede; Praharjo, Ardik (Jurnal Inovasi Ekonomi)
This study aims to determine the effect of entrepreneurial orientation and knowledge sharing on innovation and business performance on creative industry-based SMEs in Malang City. Entrepreneurial orientation is very important because the creative industry currently has an important role in building the economy. The type of research used is explanatory research using hypothesis testing and quantitative approaches. The number of samples in this study amounted to 57 respondents who were creative industry-based SMEs in Malang City. The research uses descriptive statistics and path analysis. The results of the study show that there is a significant influence between entrepreneurial orientation and knowledge sharing on business performance with innovation capability as a mediating variable.